Could Social Bots Pose a Threat to Public Health? - Allem, Jon-Patrick; Ferrara, Emilio (American Journal of Public Health, 2018)
The article focuses on the potential threat social bots, or automatic social media accounts utilizing artificial intelligence to promote specific products or ideas on social media, pose to public health. It comments on the relative lack of studies on social bots and mentions articles on the promotion of electronic cigarettes by social bots. It mentions proposed legislation in California that would require social bots to be easily identified and linked to a specific human user.